An Empirical Comparison of Human Value Models - Hanel, Paul H. P.; Litzellachner, Lukas F.; Maio, Gregory R. (Frontiers in Psychology, 2018)
Over the past century, various value models have been proposed. To determine which value model best predicts prosocial behavior, mental health, and pro-environmental behavior, we subjected seven value models to a hierarchical regression analysis. A sample of University students (N = 271) completed the Portrait Value Questionnaire (Schwartz et al., 2012), the Basic Value Survey (Gouveia, Milfont, Fischer, & Santos, 2008) and the Social Value Orientation scale (Van Lange, De Bruin, Otten, & Joireman, 1997). Additionally, they completed the Values Survey Module (Hofstede & Minkov, 2013), Inglehart’s (1977) materialism – postmaterialism items, the Study of Values, 4th edition (Allport, Vernon, & Lindzey, 1960; Kopelman, Rovenpor, & Guan, 2003) and the Rokeach (1973) Value Survey. However, because the reliability of the latter measures was low, only the PVQ-RR, the BVS, and the SVO where entered into our analysis. Our results provide empirical evidence that the PVQ-RR is the strongest predictor of all three outcome variables, explaining variance above and beyond the other two instruments in almost all cases. The BVS significantly predicted prosocial and pro-environmental behavior, while the SVO only explained variance in pro-environmental behavior.